203k views
5 votes
What is the sum for 6-2(x+6)=3x+4

User Geoff Rich
by
5.5k points

2 Answers

2 votes

Answer:

x = -2

Explanation:

6 - 2(x + 6) = 3x + 4

6 - 2x - 12 = 3x + 4

Combine like terms;

-6 - 2x = 3x + 4

Add 6 to both sides

-6 - 2x = 3x + 4

+6 + 6

Subtract 3x from both sides

-2x = 3x + 10

-3x -3x

-5x = 10

Divide both sides by -5

x = -2

User Debracey
by
4.8k points
0 votes
x = -2

just cuz it is isk



User Kevin Kalitowski
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.